2005
DOI: 10.2190/43re-qm05-7nvf-mkq6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing How Diversity Affects Students' Interest in Social Change

Abstract: As the country's racial/ethnic minority representation increases, colleges and universities have increasingly sought to diversify their enrollments in order to better prepare all students to live and work in a diverse democracy. However, diversification may negatively affect campus climate and undergraduate peer relations leading to both increased racial tensions and to lower levels of satisfaction and retention for both minority and majority students. This study examined the effects of students' entry charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Two studies were excluded from the meta-analysis because they analyzed subsamples of the Preparing College Students for a Diverse Democracy data set (Hurtado & Ponjuan, 2005;Kotori, 2009); other research had already examined the relationship between the same diversity experiences and civic outcomes using the full sample of this data set (Engberg, 2007;Hurtado, 2005). Two additional studies were excluded because the diversity experiences occurred in high school (Engberg, Meader, & Hurtado, 2003;Malaney & Berger, 2005). Another study was excluded because it reported only unstandardized coefficients and there was not sufficient information in the article to calculate standardized effects (Yamamura & Denson, 2005).…”
Section: Data Sources and Sampling Proceduresmentioning
confidence: 99%
“…Two studies were excluded from the meta-analysis because they analyzed subsamples of the Preparing College Students for a Diverse Democracy data set (Hurtado & Ponjuan, 2005;Kotori, 2009); other research had already examined the relationship between the same diversity experiences and civic outcomes using the full sample of this data set (Engberg, 2007;Hurtado, 2005). Two additional studies were excluded because the diversity experiences occurred in high school (Engberg, Meader, & Hurtado, 2003;Malaney & Berger, 2005). Another study was excluded because it reported only unstandardized coefficients and there was not sufficient information in the article to calculate standardized effects (Yamamura & Denson, 2005).…”
Section: Data Sources and Sampling Proceduresmentioning
confidence: 99%
“…However, the related notion of increased respect and tolerance for diversity has been found to be a key outcome related to college attendance (Astin, 1993;Bowen,1977;Hu & Kuh, 2003;Pascarella et al, 2004;Winter, McClelland, & Stewart, 1981). Furthermore, students from lower socioeconomic backgrounds have been found to come to campus particularly eager to engage in democratic related initiatives (Malaney & Berger, 2004). While increased tolerance and interest in democracy are not necessarily identical to validation of dissent, they often accompanied the types of dissent found in this present study.…”
Section: Validating Dissentmentioning
confidence: 50%